Liquid phase synthesis and morphological investigation of Bi2Sr2CaCu2O8+d superconductor films - Rillera, Hannah P.
A liquid phase deposition technique was studied for synthesis of Bi-2212 thin film. Bi¬2212 powders were deposited on top of MgO substrates by sedimentation from an acetone solution. Film growth was done by melting the Bi-2212 powders followed by crystallization in a furnace. The effect of temperature and time growth parameters, particularly the cooling rate was investigated. Film growth using polished (smooth) substrate was compared to growth on unpolished (rough) substrate, in producing more continuous and smoother films. Film growth from a liquid phase between two substrates was also investigated. This was done to improve the wetting for film growth on polished substrates. Film planarization by mechanical lapping/polishing and etching by plasma ion shower were explored to reduce film thickness and produce smoother surface. The morphology and composition of films were investigated using scanning electron microscopy, energy-dispersive x-ray analysis, x-ray diffraction and resistance vs. temperature measurement. The liquid phase deposition technique is an efficient way to grow thin films with the desired composition of the films obtained reproducibly. Smoothness, crystallinity and homogeneity of morphology can also be controlled from the temperature and time growth parameters. This shows that this method can be used for film growth for superconductor device application.
Computer print out.